Epstein-Barr Virus-Associated T and NK-Cell Lymphoproliferative Diseases - Kim, Wook Youn; Montes-Mojarro, Ivonne A.; Fend, Falko; Quintanilla-Martinez, Leticia (Frontiers in Pediatrics, 2019)
EBV-associated T and NK-cell lymphoproliferative diseases (EBV-T/NK LPDs) are characterized by the transformation and proliferation of EBV-infected T or NK cells. The 2016 revised World Health Organization classification recognizes the following EBV-positive lymphoproliferative disorders (LPD): chronic active EBV infection (CAEBV) of T- and NK-cell type (cutaneous and systemic forms), systemic EBV-positive T-cell lymphoma of childhood, aggressive NK-cell leukemia, extranodal NK/T-cell lymphoma, nasal type, and the new provisional entity primary EBV-positive nodal T/NK-cell lymphoma. EBV-associated hemophagocytic lymphohistiocytosis (HLH), although not included in the WHO classification because it is a reactive, inflammatory disease, is included in this review because it can be life-threatening and may have overlapping features with other EBV+ T/NK LPDs. EBV+ T/NK LPDs are rare diseases difficult to diagnose and manage properly, because some LPDs have unusual presentations, and discrepancies between clinical and histological findings might be encountered. Furthermore, EBV+ T/NK disorders share some clinico-pathological features, and may evolve into other categories during the clinical course, including malignant transformation of CAEBV. Here, we review the EBV+ T/NK LPDs in terms of their definitions, clinical features, histology, immunophenotype, molecular findings, and pathogenesis. This review aims to increase our understanding and awareness of the differential diagnosis among the different EBV+ T/NK LPDs. New insights into the genetic characteristics of these disorders will also be discussed.